Complex Trait Loci in Maize Enabled by CRISPR-Cas9 Mediated Gene Insertion - Gao, Huirong; Mutti, Jasdeep; Young, Joshua K.; Yang, Meizhu; Schroder, Megan; Lenderts, Brian; Wang, Lijuan; Peterson, Dave; St. Clair, Grace; Jones, Spencer; Feigenbutz, Lanie; Marsh, Wally; et al. (Frontiers in Plant Science, 2020)
Modern maize hybrids often contain biotech and native traits. To-date all biotech traits have been randomly inserted in the genome. Consequently, developing hybrids with multiple traits is expensive, time-consuming and complex. Here we report using CRISPR-Cas9 to generate a Complex Trait Locus (CTL) to facilitate trait stacking. A CTL consists of multiple preselected sites positioned within a small well-characterized chromosomal region where trait genes are inserted. We generated individual lines, each carrying a site-specific insertion landing pad that was targeted to a preselected site and capable of efficiently receiving a transgene via recombinase-mediated cassette exchange. We demonstrated that two traits residing at different sites within a CTL can be combined via genetic recombination. CTL technology is a major step forward in the development of multi-trait maize hybrids.